Protein-Tyrosine Phosphatase 1B as a Potential Drug Target for Obesity - Dadke, Shrikrishna; Chernoff, Jonathan (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2003)
Obesity is increasing at an alarming rate and is considered by the World Health Organization as one of the top 10 epidemics worldwide. Resistance to leptin and insulin are likely to play a central role in obesity; thus, blocking inhibitors of these signaling pathways could prove useful in treating this disorder. Several lines of evidence have converged on protein tyrosine-phosphatase 1B (PTP1B) as one of the most important negative regulators of leptin as well as insulin signaling. Therefore, PTP1B appears to be a promising therapeutic candidate for the treatment of obesity. In this review, we discuss the role of PTP1B in leptin and insulin signaling, as well as its potential as a drug target in the treatment of obesity.
Keywords: type 2 diabetes mellitus